Corporate Governance Failure in the Use of Influencer Content: Ethical and Legal Analysis - Andi Joshua Saputra Valentino; Agus Satory (Majapahit Journal of Islamic Finance and Management, 2026)
The development of digital marketing has created a new phenomenon in the form of the unauthorized use of influencer content for commercial purposes, which reflects the failure of corporate governance at the operational level. This study aims to examine the practice of unauthorized use of influencer content from a business ethics perspective, analyze the legal implications that arise, explain the role of corporate governance failure, and provide recommendations for ethical and sustainable digital marketing practices. The research uses a qualitative approach with an empirical experience-based case study design, in which data is collected through participatory observation and literature study, then analyzed using Agency Theory, Stewardship Theory, and the principles of business ethics and Good Corporate Governance. The results show that the practice of using content without permission violates the principles of fairness, transparency, and responsibility in business ethics, and has the potential to violate the Copyright Law, Personal Data Protection Law, and provisions against unlawful acts. Governance failures occur due to the absence of legal verification procedures, weak coordination between marketing and legal functions, and the absence of a stewardship culture that respects stakeholder rights. Through the lens of Agency Theory, this case reflects the uncontrolled opportunistic behavior of agents, while Stewardship Theory shows the absence of moral values in the organizational culture. The resolution of disputes through public pressure indicates the weakness of internal governance mechanisms as a preventive system.